Penetapan Kadar Nikotin pada Perokok Aktif di Kelurahan Duren Jaya Kecamatan Bekasi Timur - Laila Utari Zahra; Elfira Maya Sari; Ria Amelia (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Nicotine is the main chemical substance found in cigarettes and has toxic and addictive properties. Exposure to nicotine in active smokers can cause various health problems, including respiratory and cardiovascular disorders and dependence. The prevalence of active smokers in RT 08 RW 05, Duren Jaya Village, East Bekasi Subdistrict is quite high. However, data on nicotine levels in the bodies of active smokers remain very limited. This study aims to determine the nicotine levels in active smokers in Duren Jaya Village, RT 08 RW 05, Bekasi Timur District, using urine samples. The research method employs a descriptive design with a cross-sectional approach. Urine samples were collected from 30 male active smokers aged over 35 years who had smoked for at least 15 years. Nicotine levels were measured at the Jakarta Regional Health Laboratory using Gas Chromatography-Mass Spectrometry (GC-MS). Data were analyzed descriptively using SPSS version 22. The study included 30 male respondents (100%) with an average age of 41 years. The analysis results showed nicotine levels ranging from 59.908 ng/mLto 459.941 ng/mL, with the majority of respondents falling into the category of active smokers based on the biological threshold for nicotine levels. It can be concluded that the results obtained indicate that these levels correspond to active smokers using light tobacco.